Sunk Costs, Depreciation, and Industry Dynamics - Gschwandtner, Adelina; Lambson, Val E. (The Review of Economics and Statistics, 2012)
Two of the most robust results from dynamic competitive models of industrial organization suggest that higher-sunk-cost industries should exhibit higher intertemporal variability in the market value of their firms and lower intertemporal variability in the size of their industries. These predictions have done well empirically. This paper argues on theoretical and empirical grounds that depreciation generates countervailing effects.